ANALISIS MODEL PERSAMAAN STRUKTURAL KEPUASAN PELAYANAN SEBAGAI STRATEGI MENCIPTAKAN PELAYANAN PRIMA PADA RUMAH SAKIT TELOGOREJO SEMARANG - Hidayati, Retno (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2002)
This study is aimed to analyze the factors influence towards the healthcare satisfaction as perceived by the inpatient and to formulate the best fit strategy to serve the hospitalized patients.The stratified random sampling was used to withdraw 140 inpatients for this study. The data that was collected from survey, observation, and from documentation was estimated with Structural Equation Model (SEM) and found that service satisfaction is significantly influenced by service quality and life satisfaction, while the service quality is affected by inputs, environment, and work process.Man - power is found as the most important component for inputs and has high Loading Factor ( 1,039 ). Moreover, man - power is considered as the most dominant factor to influence the service quality and service satisfaction since it has very low probability of significance ( 0,000 ).This study recommends that the excellent service strategy could be formulated by considering the aspect of man - power resources. Type, number, and qualification of the man - power operation workers should be appointed according to the standard of personel in order to fulfil the needs of the patients.